Games as a Form of Career Guidance - Sushkova, Aigul Rafailevna; Valeeva, Rezeda Rafailevna; Davydov, Alexandr Evgenievich (Journal of History Culture and Art Research, 2019)
The authors of the article analyzed the scientific research on the use of methods and gamification techniques in career guidance and concluded that it is necessary to work out career guidance games, make sure that elements of physical activity are included in career guidance games, since the board career guidance games do not take into account the “hyperactivity” of the modern generation. The article presents the results of the analysis of career guidance work in the monotown (Nizhnekamsk, The Republic of Tatarstan), identifies factors of its low efficiency: a formal approach to the development of career guidance activities, absence of innovative forms of work in practice, reluctance of managers of enterprises and organizations to cooperate with educational organizations using new forms of career guidance, a low number of highly-qualified and motivated professionals working with innovative methods of career guidance. The study made it possible to identify problems in the implementation of career guidance projects in the monotown. These included: actually no chance of conducting professional tests in real production conditions; provocative policy of the management of enterprises, expressed in the unwillingness to take responsibility for safety of participants in career guidance projects; the lack of personnel in organizations capable of organizing and conducting professional tests in production conditions; the lack of corporate personnel policies of city-forming enterprises in the field of career guidance for children and youth, corporate programs for conducting professional samples. The paper describes the proprietary methodology of conducting professional samples in the form of a quest game which allows acquainting school-age children with the professions of city-forming enterprises in the monotown. Besides, measures to systematize and increase the effectiveness of career guidance work in single-industry conditions are proposed.